Stakeholders' engagement in co-producing policy-relevant knowledge to facilitate employment for persons with developmental disabilities - Akram Khayatzadeh-Mahani; Krystle Wittevrongel; Lisa Petermann; Ian D. Graham; Jennifer D. Zwicker (BMC, 2020)
Abstract Background Persons with developmental disabilities (PWDD) face a number of individual, environmental and societal barriers when seeking employment. Integrated knowledge translation (IKT) involves ongoing and dynamic interactions between researchers and stakeholders for the purpose of engaging in mutually beneficial research to address these types of multi-faceted barriers. There is a knowledge gap in the IKT literature on effective stakeholder engagement strategies outside of the dissemination stage to inform policy. In this paper, we report on a number of engagement strategies employed over a 2-year period to engage a wide range of stakeholders in different stages of an IKT project that aimed to investigate the 'wicked' problem of employment for PWDD. Method Our engagement plan included multiple linked strategies and was designed to ensure the meaningful engagement of, and knowledge co-production with, stakeholders. We held two participatory consensus-building stakeholder policy dialogue events to co-produce knowledge utilising the nominal group technique and the modified Delphi technique. A total of 31 and 49 stakeholders engaged in the first and second events, respectively, from six key stakeholder groups. Focused engagement strategies were employed to build on the stakeholder dialogues for knowledge mobilisation and included a focus group attended only by PWDD, a stakeholder workshop attended only by policy/decision-makers, a webinar attended by human resources professionals and employers, and a current affairs panel attended by the general public. Results Our findings suggest that the level of engagement for each stakeholder group varies depending on the goal and need of the project. Our stakeholder dialogue findings highlight the inherent challenges in co-framing and knowledge co-production through the meaningful engagement of multiple stakeholders who hold different ideas and interests. Focused outreach is needed to foster relationships and trust for meaningful engagement. Conclusions In addition to providing guidance on how to implement adaptable meaningful engagement strategies, these findings contribute to discussions on how IKT projects are planned and funded. More studies to explore effective mechanisms for engaging a wide range of stakeholders in IKT research are needed. More evidence of successful engagement strategies employed by researchers to achieve meaningful knowledge co-production is also key to advancing the discipline.